1997
DOI: 10.1038/sj.mp.4000256
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of bipolar disorder at the human serotonin transporter gene (hSERT; 5HTT)

Abstract: The human serotonin transporter gene (hSERT) is a strong candidate for involvement in the pathogenesis of mood disorder and, using a UK Caucasian case-control sample, Collier et al found a significant association between bipolar disorder and the 12 allele of the VNTR polymorphism in intron 2 of this gene. In a European collaborative sample, Collier et al found a significant association between affective disorder and a functional deletion polymorphism in the promoter of hSERT. We have undertaken association stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
105
1
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 0 publications
9
105
1
1
Order By: Relevance
“…SERPR long and short allele frequencies were, respectively, 0.51 and 0.49, similar to those of previously published samples in Caucasians 45,59,69,70 and similar to those observed in our Italian sample (0.57 and 0.43, respectively). 60 Italian and Greek samples were not different in terms of SERTPR genotypes frequencies (w 2 ¼ 4.3; df ¼ 2; P ¼ 0.1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…SERPR long and short allele frequencies were, respectively, 0.51 and 0.49, similar to those of previously published samples in Caucasians 45,59,69,70 and similar to those observed in our Italian sample (0.57 and 0.43, respectively). 60 Italian and Greek samples were not different in terms of SERTPR genotypes frequencies (w 2 ¼ 4.3; df ¼ 2; P ¼ 0.1).…”
Section: Resultssupporting
confidence: 92%
“…The gene coding for it has been proposed as a possible candidate for involvement in the pathogenesis of major psychoses. A functional polymorphism in the upstream regulatory region of the gene has been associated with both major depressive and bipolar disorders, [43][44][45] although subsequent studies did not replicate these results. [46][47][48][49][50][51][52][53][54][55][56][57][58] The polymorphism in the upstream is a deletion/insertion (SERTPR) located exactly at the 5 0 -flanking regulatory region of serotonin transporter gene on chromosome 17q11.2.…”
Section: Introductionmentioning
confidence: 99%
“…48,59 The 31 papers finally selected reported 43 studies related to the review objective in total since each paper frequently reported several separate studies. In total, 17 population-based studies 9,14,33,34,38,46,50,51,56,60,61,66,[68][69][70] and six family-based studies 12,32,42,53,63,74 were about 5-HTTLPR. A total of 16 population-based studies 27,33,35,38,41,47,[49][50][51]54,56,58,60,61,70,75 and four family-based studies 12,52,57,63 were about the intron 2 VNTR.…”
Section: Resultsmentioning
confidence: 99%
“…51 The remaining studies mentioned that the sample was ethnically homogeneous. 9,14,34,35,49,54,58,61,68,70,75 5-HTTLPR meta-analysis In total, 17 population-based studies comprised 1712 cases (ie 3424 alleles) and 2583 controls, whereas six family-based studies comprised 587 trios. Summaries are shown in the Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-HTT has been directly implicated in depression by the finding that brain 5-HTT binding density is reduced in brains and platelets of depressed patients (e.g., Nemeroff et al 1994;Malison et al 1998;Mann et al 2000). Moreover, a number of studies have found an association between genetic variation in the regulatory region of the 5-HTT gene and depression (e.g., Battersby et al 1996; Collier et al 1996a,b;Furlong et al 1998;Rees et al 1997;Menza et al 1999; but see Seretti et al 1999). The 5-HTT is also a major target for many antidepressant drug treatments (Blakely et al 1991;Ramamoorthy et al 1993).…”
mentioning
confidence: 99%